Research and Application of Fracturing Testing Technology in a South-West Weizhou Oilfield Shale Oil Exploration Well - Wenbo Meng; Yan Jin; Yunhu Lu; Guanlong Ren; Shiming Wei (Energies)
A numerical analysis model for sand-mudstone interbedded fracturing based on field application in South China is presented in this paper. The proposed model can analyze the influence laws of different longitudinal lithology changes, stress difference changes, different interlayer positions, and fracturing fluid construction parameters on fracture characteristics. Based on the study of fracture characteristics of low-modulus mudstone, a set of layered stress loading experimental devices was independently designed and developed. Experimental analysis shows that the stress difference has a limited limiting effect on the interlayer propagation of hydraulic fracturing fractures in the Weizhou Formation, and the fracture height is prone to interlayer propagation. The injection of high-rate and high-viscosity fracturing fluid has a significant impact on the hydraulic fracture surface penetration. Numerical simulation analysis shows that the smaller the elastic modulus of the mudstone interlayer and the lower the minimum horizontal principal stress compared to the sandstone layer, the more favorable it is for fracture propagation. Field application showed that the highest injection rate of the fracturing pump in well A was 7 m3/min for south-west Weizhou oilfield shale oil. The interpretation results of the acoustic logging after fracturing showed obvious response characteristics of the formation fractures, and the farthest detection fracture response well distance was 12 m, indicating a good fracturing transformation effect and providing technical support for subsequent offshore shale oil fracturing construction.